2011
DOI: 10.1063/1.3556123
|View full text |Cite
|
Sign up to set email alerts
|

Surface nanostructuring of laser ablated copper in ambient gas atmosphere and a magnetic field

Abstract: A comprehensive study on deposition of copper nanoclusters back on to the laser ablated target in combined ambient of gas and a magnetic field is reported. The characteristics and mechanism of the inverse plume deposition are investigated by characterizing the laser ablated plasma plume using time resolved imaging and optical emission of the plume. The morphology of the deposited particles in presence of magnetic field depends on the nature of the ambient gas used; the elliptical shape of reverse deposited par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…40 The decrease in electron density with time for both ns and fs LPP is due to the plasma expansion and three-body recombination of electrons with their parent ions. 30,44,45 Unnikrishnan et al conducted studies on the electron density of copper from a ns LPP and has found that the temporal profile follows an exponential decay. 38 Also, Xu et al conducted temporal studies using fs LPP on a Pb target and also observed exponential electron density decay for fs LPP.…”
Section: A Time Evolution Of Temperature and Densitymentioning
confidence: 99%
“…40 The decrease in electron density with time for both ns and fs LPP is due to the plasma expansion and three-body recombination of electrons with their parent ions. 30,44,45 Unnikrishnan et al conducted studies on the electron density of copper from a ns LPP and has found that the temporal profile follows an exponential decay. 38 Also, Xu et al conducted temporal studies using fs LPP on a Pb target and also observed exponential electron density decay for fs LPP.…”
Section: A Time Evolution Of Temperature and Densitymentioning
confidence: 99%
“…Initially, plasma gets energized and the free expansion of the plasma plume results in decrease in conductivity of the plasma according to the relation which in turn decreases the magnetic diffusion time into the plasma causing the polarization of the plasma. 16,26 The electric field E is established perpendicular to both magnetic field (B) and the plasma velocity. The plasma moves across the B field byẼ ÂB drift with velocity ðẼ ÂBÞ=B 2 .…”
Section: Resultsmentioning
confidence: 99%